Lowering the scale of Pati-Salam breaking through seesaw mixing - Matthew J. Dolan; Tomasz P. Dutka; Raymond R. Volkas (Journal of High Energy Physics, 2021)
Abstract We analyse the experimental limits on the breaking scale of Pati-Salam extensions of the Standard Model. These arise from the experimental limits on rare-meson decay processes mediated at tree-level by the vector leptoquark in the model. This leptoquark ordinarily couples to both left- and right-handed SM fermions and therefore the meson decays do not experience a helicity suppression. We find that the current limits vary from O $$ \mathcal{O} $$ (80–2500) TeV depending on the choice of matrix structure appearing in the relevant three-generational charged-current interactions. We extensively analyse scenarios where additional fermionic degrees of freedom are introduced, transforming as complete Pati-Salam multiplets. These can lower the scales of Pati-Salam breaking through mass-mixing within the charged-lepton and down-quark sectors, leading to a helicity suppression of the meson decay widths which constrain Pati-Salam breaking. We find four multiplets with varying degrees of viability for this purpose: an SU(2) L/R bidoublet, a pair of SU(4) decuplets and either an SU(2) L or SU(2) R triplet all of which contain heavy exotic versions of the SM charged leptons. We find that the Pati-Salam limits can be as low as O $$ \mathcal{O} $$ (5–150) TeV with the addition of these four multiplets. We also identify an interesting possible connection between the smallness of the neutrino masses and a helicity suppression of the Pati-Salam limits for three of the four multiplets.